2007
DOI: 10.1007/s00264-007-0364-3
|View full text |Cite
|
Sign up to set email alerts
|

Total hip arthroplasties: What are the reasons for revision?

Abstract: Primary total hip arthroplasties have reported success rates of greater than 95% in many series with a longer than 10-year follow-up. Revision total hip arthroplasty due to such factors as increased high-activity levels, younger patients undergoing the procedure and increasing life expectancy has become more prevalent. An understanding of the mechanisms and timing of total hip arthroplasty failure can direct efforts aimed at reducing revision rates. This study was conducted to evaluate the indications for revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
229
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 401 publications
(259 citation statements)
references
References 32 publications
5
229
1
3
Order By: Relevance
“…Our findings of indications for revision echo previous epidemiologic studies of revision total joint arthroplasties [7,8]; however, our findings for revision THAs differ from prior observational cohort studies [3,54] and international registry reports [33,43] that identified aseptic loosening, bearing surface wear, and osteolysis as primary causes of TKA failure. Likewise, our revision TKA findings differ from those of prior reports implicating aseptic etiologies, including polyethylene wear, prosthetic loosening, and instability as the primary mechanisms for failed TKA [16,36,37,41,51,52].…”
Section: Discussionsupporting
confidence: 63%
“…Our findings of indications for revision echo previous epidemiologic studies of revision total joint arthroplasties [7,8]; however, our findings for revision THAs differ from prior observational cohort studies [3,54] and international registry reports [33,43] that identified aseptic loosening, bearing surface wear, and osteolysis as primary causes of TKA failure. Likewise, our revision TKA findings differ from those of prior reports implicating aseptic etiologies, including polyethylene wear, prosthetic loosening, and instability as the primary mechanisms for failed TKA [16,36,37,41,51,52].…”
Section: Discussionsupporting
confidence: 63%
“…Aseptic loosening continues to be the predominant mode of failure of hip arthroplasty with over 50% of the revisions being performed for this reason alone [42]. Particulate debris generated by wear of the liner in implants with metal-on-polyethylene bearing surfaces is one of the main stimulators of periprosthetic osteolysis and eventual aseptic loosening [8,17,20,29].…”
Section: Introductionmentioning
confidence: 99%
“…Second-decade failure of THA components has implicated specific acetabular component designs [1,12,15] and undersizing cementless femoral components [1]. Mechanical weakness of conventional polyethylene resulting from sterilization processes also can contribute to an increased risk of prosthetic failure [19,25,28]. Higher failure rates also have been associated with acetabular component malposition, younger age, and male gender [6,21,29].…”
Section: Discussionmentioning
confidence: 99%